Advances in Spatial Data Handling and GIS 14th International Symposium on Spatial Data Handling - Yeh, Anthony G.O.; Shi, Wenzhong; Leung, Yee.; Zhou, Chenghu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book provides a cross-section of cutting-edge research areas being pursued by researchers in spatial data handling and geographic information science (GIS). It presents selected papers on the advancement of spatial data handling and GIS in digital cartography, geospatial data integration, geospatial database and data infrastructures, geospatial data modeling, GIS for sustainable development, the interoperability of heterogeneous spatial data systems, location-based services, spatial knowledge discovery and data mining, spatial decision support systems, spatial data structures and algorithms, spatial statistics, spatial data quality and uncertainty, the visualization of spatial data, and web and wireless applications in GIS.
Modeling Space and Time -- Generalization and Indexing -- Pattern Recognition and Object Extraction -- Location-Based Service -- Application of GIS and Remote Sensing.
Keywords: Geography; Remote sensing; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Signal, Image and Speech Processing; Remote Sensing/Photogrammetry.